Math, asked by nishahasbun52, 10 months ago

please solve this question for me​

Attachments:

Answers

Answered by BrainlyTornado
2

QUESTION:

If Sin θ + Cos θ = m, then prove that Sin⁶ θ Cos⁶ θ = [4 - 3(m² - 1)²] / 4, where m² ≤ 2.

GIVEN:

  • Sin θ + Cos θ = m

  • m² ≤ 2

TO PROVE:

\sf Sin^6 \ \theta + Cos^6 \ \theta = \dfrac{3-4(m^2-1)^2}{4}

EXPLANATION:

\sf \sf Sin^6 \ \theta + Cos^6 \ \theta = (Sin^2 \ \theta)^3 + (Cos^2 \ \theta)^3

\boxed{\bold{\gray{A^3 + B^3 = (A + B)(A^2 - AB + B^2)}}}

\sf \leadsto  (Sin^2 \ \theta +Cos^2 \ \theta)(Sin^4 \ \theta -Sin^2 \ \theta\ Cos^2 \ \theta+Cos^4 \ \theta)

\boxed{\bold{\gray{\large{Sin^2 \ \theta +Cos^2 \ \theta=1}}}}

\sf \leadsto  (1)(Sin^4 \ \theta -Sin^2 \ \theta \ Cos^2 \ \theta+Cos^4 \ \theta)

\sf \leadsto Sin^4 \ \theta +Cos^4 \ \theta =(Sin^2 \ \theta +Cos^2 \ \theta )^2- 2\ Sin^2 \ \theta \ Cos^2 \ \theta

\boxed{\bold{\gray{\large{Sin^2 \ \theta +Cos^2 \ \theta=1}}}}

\sf \leadsto Sin^4 \ \theta +Cos^4 \ \theta =(1)^2- 2 \ Sin^2 \ \theta \ Cos^2 \ \theta

\sf \leadsto Sin^4 \ \theta +Cos^4 \ \theta =1-2 \ Sin^2 \ \theta \ Cos^2 \ \theta

\sf Subtract \ by \ sin^2 \ \theta \ cos^2 \ \theta

\sf \leadsto Sin^4 \ \theta -Sin^2 \ \theta \ Cos^2 \ \theta+Cos^4 \ \theta = 1-3 \ Sin^2 \ \theta \ Cos^2 \ \theta

\sf Sin \ \theta + Cos \ \theta = m

Square on both sides.

\boxed{\bold{\large{\gray{(A + B)^2 = A^2 +2AB +B^2}}}}

\sf Sin^2 \ \theta + Cos^2 \ \theta+2\ sin \ \theta\ cos \ \theta = m^2

\boxed{\bold{\gray{\large{Sin^2 \ \theta +Cos^2 \ \theta=1}}}}

\sf 1+2\ sin \ \theta\ cos \ \theta = m^2

\sf 2\ sin \ \theta\ cos \ \theta = m^2-1

\sf  sin \ \theta\ cos \ \theta = \dfrac{m^2-1}{2}

Square on both sides

\sf  sin^2 \ \theta\ cos^2\ \theta = \dfrac{(m^2-1)^2}{4}

Substitute the value of Sin² θ + Cos² θ

\sf  1-3 \dfrac{(m^2-1)^2}{4}

\sf  \dfrac{4}{4} -3 \dfrac{(m^2-1)^2}{4}

\sf \dfrac{4-3(m^2-1)^2}{4}

\sf Sin^6 \ \theta + Cos^6 \ \theta = \dfrac{3-4(m^2-1)^2}{4}

HENCE PROVED.

Similar questions